Penerapan Analisis SWOT terhadap Pencapaian Target Pembiayaan Mikro Syariah pada BPRS Mitra Agro Usaha di Bandar Lampung - Hasan, Afif Somantri; Ratmono, Ratmono (Jurnal Manajemen DIVERSIFIKASI, 2021)
Talking about the perception of our society about the Bank, we can be sure that the perception that arises is that the Bank is an institution for saving money. The condition in the field states that not all levels of society have made maximum use of bank products. The condition of banking is one of the sectors which is expected to be able to play an active role in supporting national development activities. This role is manifested in its main function as an intermediary institution or intermediary institution between debtors and creditors. Thus, economic actors who need funds to support their activities can be fulfilled and then the wheels of the economy move. The formulation of the problem in this study is "How is the application of SWOT analysis to the achievement of financing targets in BPRS Agro Business Partners?". This research is a descriptive exploratory study with an expose facto approach, because it aims to describe the state of the phenomena that occur in the field. The technique used in data collection in this research is using literature study, field study, and questionnaires. This study uses a SWOT analysis. The first step is to formulate a strategy, namely SO, WO, ST, and WT. The results of the study indicate that the BPRS Mitra Agro Usaha Bandar Lampung has strengths, namely operating with the sharia system, strategic location, short and fast bureaucracy, and has a legal entity. The weakness is that it is difficult to find human resources in the marketing sector and as a new bank that is not widely known by the public. Meanwhile, the opportunities are good business prospects, approaches with government agencies, and small business activities are very potential within the BPRS MAU. The threats are competition between banks and competition at the margin level.